2015
DOI: 10.1007/s40119-015-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use of Antihypertensive Agents and Risk of Breast Cancer: A Population-Based Case–Control Study

Abstract: IntroductionTo evaluate the risk of breast cancer associated with long-term use of antihypertensive agents (AHs) in Taiwanese women with hypertension.MethodsA search of the Taiwan National Health Insurance Research Database identified 330,699 patients with hypertension who were treated with antihypertensive drugs between January 1, 1998 and December 31, 2011. Logistic regression models were used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) between the use of AHs and breast cancer risk, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 24 publications
(26 reference statements)
2
33
0
Order By: Relevance
“…A number of epidemiological studies have also been conducted to assess their possible influence on breast cancer incidence and outcomes. With respect to incident breast cancer, the results of prior studies are mixed, with some (611), but not all (1216), observing use of CCBs and diuretics to be associated with an increase in risk. Neither of the two studies of these two classes of medications observed an association with breast cancer outcomes (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…A number of epidemiological studies have also been conducted to assess their possible influence on breast cancer incidence and outcomes. With respect to incident breast cancer, the results of prior studies are mixed, with some (611), but not all (1216), observing use of CCBs and diuretics to be associated with an increase in risk. Neither of the two studies of these two classes of medications observed an association with breast cancer outcomes (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…However, the highly inconsistent evidence generated by such studies offer little help in shedding light on this issue, especially regarding the cardiovascular safety of thiazolidinediones and the effect of incretin‐based therapies on pancreatitis . Our worry is that such and other similar discouraging situations may undermine the credibility of observational research, particularly that based on HCU databases. We believe that not only are observational studies based on HCU data have an enormous potential in orienting healthcare decisions and in evaluating the safety of medication but also that systematic uncertainty needs to be accurately controlled in such studies to generate consistent evidence …”
Section: Discussionmentioning
confidence: 99%
“…20,21,[23][24][25][26][27][28][29][30][31][32][33][34] The characteristics of the studies analysed, as well as the values from the abstractions noted above which comprise the raw data used to calculate the effect size, are presented in Tables 1 and 2. [21][22][23]25,28,29,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…20,21,23-34 The characteristics of the studies analysed, as well as the values from the abstractions noted above which comprise the raw data used to calculate the effect size, are presented inTables 1 and 2 [21][22][23]25,28,29,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. A supplementary Appendix C consisting of studies, which were quantitatively analysed and then excluded with reasons, is also provided.…”
mentioning
confidence: 99%